2018
DOI: 10.1101/366187
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bloodstream Infection with Extended-spectrum Beta-lactamase–producingEscherichia coli: the role of virulence genes

Abstract: 27 Background: Various bacterial putative virulence factors are involved in the 28 pathogenesis of bacterial infection. However, the effect of comorbidities or infection 29 syndrome in the association of virulence factors and mortality remains inconclusive. 30 Method: This study addressed whether specific sequence type (ST) and virulence 31 factors of extended-spectrum beta-lactamase-producing Escherichia coli (ESBL-EC) 32 are associated with different outcomes in patients with bloodstream infection.121 33 adu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(25 reference statements)
1
0
0
Order By: Relevance
“…In addition, in some other studies, iutA gene positivity has been detected at the rates of 67.5 to 80.2% in E. coli urinary and blood isolates. 27 38 In our study, the iutA gene was found in 92% of urine, and 90% of blood, isolates. In line with the results, it can be stated that the iucD and iutA genes actually demonstrate the importance of iron retrieval systems during pathogenesis.…”
Section: Discussionsupporting
confidence: 46%
“…In addition, in some other studies, iutA gene positivity has been detected at the rates of 67.5 to 80.2% in E. coli urinary and blood isolates. 27 38 In our study, the iutA gene was found in 92% of urine, and 90% of blood, isolates. In line with the results, it can be stated that the iucD and iutA genes actually demonstrate the importance of iron retrieval systems during pathogenesis.…”
Section: Discussionsupporting
confidence: 46%